To prepare an initial framework of Employee Recognition Program for Siam City Cement (Bangladesh) Limited. - Adneen, Maria (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.